2018
DOI: 10.1073/pnas.1721523115
|View full text |Cite
|
Sign up to set email alerts
|

Time-evolving genetic networks reveal a NAC troika that negatively regulates leaf senescence in Arabidopsis

Abstract: SignificanceLeaf senescence is regulated in a complex manner, involving time-dependent interactions with developmental and environmental signals. Genetic screens have identified key regulators of senescence, particularly late-stage senescence regulators. Recently, time-course gene-expression and network analyses, mostly analyses of static networks, have predicted many senescence regulators. However, senescence is defined by time-evolving networks, involving the temporal transition of interactions among senesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
132
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(137 citation statements)
references
References 49 publications
5
132
0
Order By: Relevance
“…Transcriptome analysis of the double mutant confirmed upregulation of many SA-pathway genes (Figure 8D-E), which likely explains the enhanced resistance against (hemi)-biotrophic pathogens. In support of our findings, a recent study of a NAC TF network during developmental leaf senescence by (Kim et al, 2018) also linked ANAC090 to SA signalling. In that study, they identified ANAC090 as a negative regulator of SA-mediated leaf senescence and they showed that loss of ANAC090 led to increased SA levels and accelerated leaf senescence.…”
Section: Discussionsupporting
confidence: 91%
“…Transcriptome analysis of the double mutant confirmed upregulation of many SA-pathway genes (Figure 8D-E), which likely explains the enhanced resistance against (hemi)-biotrophic pathogens. In support of our findings, a recent study of a NAC TF network during developmental leaf senescence by (Kim et al, 2018) also linked ANAC090 to SA signalling. In that study, they identified ANAC090 as a negative regulator of SA-mediated leaf senescence and they showed that loss of ANAC090 led to increased SA levels and accelerated leaf senescence.…”
Section: Discussionsupporting
confidence: 91%
“…2; Supplemental Table S4), suggesting it too may play a role in regulating senescence in wheat. ANAC082 and ANAC090 form part of a NAC regulatory module that governs the shift from positive to negative regulation among NACs at a pre-senescence stage in Arabidopsis (Kim et al, 2018). However, ANAC082 and ANAC090 were not differentially expressed in Arabidopsis, and the majority of their wheat orthologs were also not differentially expressed during senescence (the third member of the regulatory module ANAC017 did not have a wheat ortholog).…”
Section: Conservation Of Senescence-related Genes Between Wheat Ricementioning
confidence: 98%
“…The purified EV protein preparation (9 µg) was desalted with SDS-PAGE loaded onto the stacking gel followed by staining and destaining. The in-gel trypsin digestion was carried out obtained by randomly permuting the WT/KO labels for all proteins, as previously described 128 .…”
Section: Comparative Proteomicsmentioning
confidence: 99%